2021
DOI: 10.3389/fendo.2021.730279
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Thyroid Nodules and Metabolic Syndrome: A Systematic Review and Meta-Analysis

Abstract: ObjectiveThyroid nodules (TNs) are a common thyroid disorder that can be caused by many factors. Several studies have investigated the relationship between TNs and metabolic syndrome (MetS), but the role of sex and age remains controversial. The purpose of this paper was to analyze published data from all relevant studies to reliably estimate the relationship between TNs and MetS.MethodsThirteen articles were included in this study; articles were identified by searching for publications until July 2021 in PubM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 44 publications
2
14
0
Order By: Relevance
“…Metabolic Syndrome is indeed associated with the prevalence of TN(s). Component diseases such as central obesity, abnormal blood pressure, hyperglycemia, and hypertriglyceridemia are also associated with thyroid nodules, a finding supported by several meta-analyses ( 25 , 29 ). However, our results did not show a correlation between low HDL - C and thyroid nodules, which is inconsistent with other conclusions ( 58 ).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Metabolic Syndrome is indeed associated with the prevalence of TN(s). Component diseases such as central obesity, abnormal blood pressure, hyperglycemia, and hypertriglyceridemia are also associated with thyroid nodules, a finding supported by several meta-analyses ( 25 , 29 ). However, our results did not show a correlation between low HDL - C and thyroid nodules, which is inconsistent with other conclusions ( 58 ).…”
Section: Discussionmentioning
confidence: 67%
“…It is worth noting that most of these risk factors are components of Metabolic Syndrome (MetS), which includes abdominal obesity; atherogenic dyslipldemia; hypertension; hyperglycemia and so on. A meta-analysis showed that a strong correlation between TN(s) and MetS in the non-iodine-deficient population ( 25 ). A study found that the thyroid was the target organs for MetS ( 3 ), and a portion of MetS patients had thyroid nodules ( 26 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies explored the association between GMD and TNs [ 20 , 21 , 22 , 23 ], but only a few of them investigated a possible sex-based association between GMD and TNs [ 24 , 25 , 26 , 27 ]. In the study by Ding et al [ 24 ], T2DM and metabolic syndrome were independently associated with TNs in females but not in males, supporting the hypothesis that sex may be an important factor influencing TN development in the general population living in a rural Chinese region.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin-resistance (IR) plays a pivotal role in causing hyperinsulinemia, which, in turn, could stimulate thyroid follicular cell proliferation [ 20 ]. Furthermore, metabolic syndrome seems to be associated with TNs [ 21 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thyroid nodules (TN) are a relatively prevalent thyroid gland disorder. 1 Palpation detects only a small number of TNs (3%-7%), While this rate is much higher in ultrasonographic examination with highresolution devices (up to 76%), 2 making it the first choice for nodule detection and investigation for potential malignancy. 3 Malignancy risk of TN has been reported to be 3.1% and 4.7% in patients with multinodular goiter and solitary TNs, respectively.…”
Section: Introductionmentioning
confidence: 99%